By the time you read this it is already too late - Theron Schmidt (Performance Philosophy)
Performance is that which attempts to hold that within which it itself is held. This may take the form of an explicit theatricality, foregrounding and reflecting upon the conditions of being seen and being heard, of the speech and appearance of an actor – which can have both dramatic as well as political dimensions (Arendt [1958] 1998; Schmidt 2017). Or it may take the form of an intentional or habitual performativity, generating the conditions which it purports to describe (Butler 2015; Paavolainen 2018).